Respuesta :

Step-by-step explanation:

Step 1:  Add 13x to both sides

[tex]x^2 + 13x = -13x + 13x - 4[/tex]

[tex]x^2 + 13x = -4[/tex]

Step 2:  Add 4 to both sides

[tex]x^2 + 13x + 4 = -4 + 4[/tex]

[tex]x^2 + 13x + 4[/tex]

Step 3:  Use Quadratic Formula

[tex]x = \frac{ -b \pm \sqrt{ b^2 - 4ac } }{2a}[/tex]

[tex]x = \frac{ -(13) \pm \sqrt{ 13^2 - 4(1)(4)} } { 2(1)}[/tex]

[tex]x = \frac{-13 \pm \sqrt{153}}{2}[/tex]

[tex]x = \frac{-13\pm3\sqrt{17} }{2}[/tex]

Answer:  [tex]x = \frac{-13\pm3\sqrt{17} }{2}[/tex]

Answer:

-0.3 and - 12.7

Step-by-step explanation:

Rewrite in quadratic form:

x2 + 13x + 4 = 0

The best approximations, given the options, are 0 and - 13

The actual solution is -

ACCESS MORE